Response of a cylindrical invisibility cloak to electromagnetic waves - Zhang, Baile (2012)
Based on electromagnetic wave scattering theory, we demonstrate that magnetic and electric surface currents are induced at the inner boundary of a cylindrical cloak by incoming waves. These surface currents have no counterparts in the coordinate transform theory. In addition, electromagnetic fields can penetrate into the concealed region under specified conditions, but carry no power. The field distribution can be unsymmetrical when a circularly polarized wave is obliquely incident onto the cloak. The far-field scattering for a nonideal cylindrical cloak is also theoretically addressed.